PENGARUH PERILAKU KEPEMIMPINAN TRANSFORMASIONAL DAN LOCUS OF CONTROL TERHADAP KEPUASAN KERJA KARYAWAN - SARJITA SARJITA (STIE Atma Bhakti, 2017)
This research aimed to know influenced of: 1) the transformational leadership toward the employees job satisfaction, 2) the locus of control toward the employees job satisfaction. This research was conducted in Bank of BRI Solo Slamet Riyadi with used sample with amount 100 respondent. Sample method with purposive random sampling. Data collecting used questioner, while data analysis technique that used instrument test consist validity test and reliability test; classic assumption test consist heteroscedasticity test, autocorrelation test, normality test, multicolinierity test; hypothesis test consist used multiple linier regression, t test, F test and determinant coefficient. The results show that: 1) the transformational leadership behavior influenced positive toward the employees job satisfaction, 2) the locus of control uninfluenced positive toward the employees job satisfaction, 3) the transformational leadership behavior and locus of control simultan influenced significant toward the employees job satisfaction, 4) coefficient determination value is 0.090, the meaning of transformational leadership behavior and locus of control influenced toward the employees job satisfaction is 9% and while its remain 91% is explained by other variable which is not involved in the regression model such as a compensation system, job load, pay and position promotion. Key word: transformational leadership behavior, locus of control, job satisfaction